Istikhdâm Namûdzaj al-Ta’allum al Ta’âwuni STAD li Tarqiyyah Mahârah al-Istimâ’ - Harahap, Fadhilah el-Wahdah; Ritonga, Mahyudin; Yasmadi, Yasmadi (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Purpose- This research aims to know the effects of listening skills by  using the Student Team Achievement Division (STAD) type cooperative learning models in Islamic Senior High School 2 Padang. Design/Methodology/Approach- This research is a quantitative experimental research where the object is students of Islamic Senior High School 2 Padang. The data in this research was obtained through observation, interview, and test. Findings- The results of this research indicate that there is an effect of  listening skills by using the STAD type cooperative learning models because there is an increase in student learning outcomes. This can be seen from the average value of the student before using the model is 60 while the average value of the student after is 83. Research Limitation/ Implications- Due to the time limits, this research couldn’t go any further. However, it obtained satisfactory results and can be expected to help develop innovative learning models for listening skill in Islamic Senior High School 2 Padang.